การพัฒนาภูมิทัศน์องค์กรในประเทศไทย - เปรมพล ตั้งเจิดจ้า (คณะสถาปัตยกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Corporate landscape refers to a type of landscape architecture used as a corporate workplace. In the mid-twentieth century, due to high urban density, several leading corporations in the United States relocated their offices to the suburbs. The planning and design of these new workplaces were exceptional and included not only the workplaces, but also residences and other amenities. Louise A. Mozingo called this new landscape "Pastoral Capitalism" and regarded it as "an American invention of the post-World war II period." The American corporate landscape got attention from a number of corporations all over the world. The concept of an innovation district recently gained popularity - as the business related to innovation and technology has advanced dramatically. The goals of this research included 1) to gather the corporate landscape projects in Thailand, and 2) to analyze their development patterns, in terms of temporal and spatial dimensions. The research located 46 corporate landscapes in Thailand; the first one was established in 1933. Considering their chronological development, the pioneering corporate landscapes in Thailand are those of service industry and state enterprise, followed by real estate industry, construction industry, and finance sector, respectively. After the 1977 economic crisis, Thailand s economy rebounded with the service industry and tourism industry. Until recently, the corporate landscapes of innovation and technology industry increases. The country s economic policy and fluctuation, along with the digital revolution seem to play a role in this trend. Regarding the locations of these corporate landscape projects, they are mostly concentrated in Bangkok and its vicinity, and the provinces in the lower Central region as well as along the coastline of the Eastern region. The urban planning regulations, the economic policy, and the concentration of the business network in Bangkok seem to play a role in this spatial pattern. This research significantly provides information and insight for the governmental agencies to develop the policies, and for the corporations to develop the idea regarding their workplace environment, in order to advocate the establishment of new and novel corporate landscapes in Thailand. Future research on recommendations for planning and design of corporate landscapes in Thailand is tremendously crucial for landscape professionals, as well as those in related fields.